Tissue culture studies, secondary metabolites and pigment extraction from Allamanda Cathartica L. / Wong Kim Fah - Wong, Kim Fah (2013)
Allamanda cathartica L. is a potential medicinal plant which starts to achieve public awareness due to its nutritional value that able to treat various types of diseases, especially in the treatment of jaundice, malaria and cancer. Tissue culture studies were undertaken to examine the effects of different plant growth regulators (PGRs) on the callus induction from leaf and stem explants of this species. Surface sterilization by mercuric (II) chloride (HgCl2) was utilized in order to surface sterilize the leaf (0.1%) and stem (0.2%) explants. The leaf and stem explants were cultured on full-strength Murashige and Skoog (MS) medium supplemented with different concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D), 6-benzylaminopurine (BAP), Naphthaleneacetic acid (NAA) or 4-amino-3,5,6-trichloropicolinic acid (picloram) alone (0.5 and 1.0 mg/L) or in combinations of 2,4-D (0.5, 1.0 and 1.5 mg/L) and BAP (0.5, 1.0 and 1.5 mg/L) or NAA (0.5 and 1.0 mg/L) and BAP (0.5 mg/L). MS basal medium was used as a control medium. From the results obtained, the leaf and stem explants cultured on 1.0 mg/L 2,4-D and 1.0 mg/L BAP gave the best callus response (100%) with yellow-white, greenish friable callus (0.3857 ± 0.0939 g and 0.0707  0.0549 g for callus fresh and dry weights) and brown-white, greenish friable callus (0.4177 ± 0.0108 g and 0.0207  0.0009 g for callus fresh and dry weights), respectively. In vitro plant regeneration from the nodal explants of A. cathartica L. was also achieved. Surface sterilization of the nodal explants by 0.2% HgCl2 was tested and the explants were cultured on MS medium supplemented with BAP at 1.0, 3.0 and 5.0 mg/L for shoot multiplication. MS basal medium was used as a control and also for shoot elongation. Microscopic studies on the surfaces of the leaf and stem specimens from in vitro and in vivo shoots were also examined using scanning electron microscope (SEM). For shoot multiplication, MS supplemented with 5 mg/L BAP gave the best response (100%) with formation of multiple shoots (6.0 ± 0.6 shoots per explant) from the nodal explants. In the PGR-free medium, the elongated shoots were developed (1.01 ± 0.07 cm) with white hairy roots. SEM micrographs showed the in vitro specimens to be cleaner in term of surfaces compared to in vivo specimens. Abundant stomata were observed on the leaf abaxial surface. The ethanolic dried and fresh extracts of the leaves, stems, petals and roots of A. cathartica L. were used and the extracts were screened for the presence of phytochemicals and their effects on 1,1-diphenyl-2-picrylhydrazyl (DPPH) was used to determine the free radical scavenging activity. Phytochemical screening of all the extracts showed the presence of reducing sugars, anthraquinones, terpenoids and steroids, glycosides and essential oils. Saponins and flavonoids were absence in the fresh and dried leaf extracts. Tannins were similarly absent from the root (dried material) and stem (fresh material) extracts. Concentrations of the plant extracts required for 50% inhibition of DPPH radical scavenging effect (IC50) were recorded as 2.40 μg/ml, 2.59 μg/ml, 4.05 μg/ml and 4.58 μg/ml for ethanolic dried extracts of roots, petals, stems and leaves, respectively. As for the ethanolic fresh extracts of roots, stems, petals and leaves, the IC50 values were recorded as 3.49 μg/ml, 4.14 μg/ml, 4.83 μg/ml and 5.04 μg/ml, respectively. Meanwhile, the positive control of ascorbic acid showed IC50 value of 3.28 μg/ml. Studies of pigment extraction and coloured coating development were also carried out for the detection of pigments and the coloured coating was developed from the natural pigments of A. cathartica L. Three extracting solvents, 0.15% HCl in 99.9% methanol, 0.01% HCl in 70% acetone and 95% ethanol in different volumes (5.0, 12.5, 20.0 and 25.0 ml) were utilized for each 1 g of plant material (leaves, stems, petals and calli) and compared. The coloured coating development was performed using the mixture of polyvinyl alcohol (PVA) solution and plant extracts (ethanol and methanol extracts) in the mixing ratio of 1:1 painted on the glass slides and cotton wools, which then proceeded with the salt and heat tests. UV-VIS spectrophotometer was used to measure the absorbance values. The pigments, chlorophyll a and chlorophyll b showed the maximum absorption in 20 ml methanol leaf extract, ethanol stem extract and acetone callus extract, whereas the carotenoid pigments present in the petals exhibited intense absorption in 5.0 ml of ethanol. The natural colours of the pigments were found to be potential new alternative sources of synthetic colourants for the paint and textile industries.